1989
DOI: 10.1128/jcm.27.1.162-167.1989
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin M, A, and G antibody response to lipopolysaccharide O antigen in symptomatic and asymptomatic Shigella infections

Abstract: The antilipopolysaccharide antibody response in sera obtained from subjects involved in 10 outbreaks of shigellosis occurring in Israeli military field units was determined by an enzyme-linked immunosorbent assay and a passive hemagglutination test. Both tests were found to be sensitive and specific for the diagnosis of shigellosis. A significant antibody response was detected in 73 to 82% of the symptomatic and 48 to 60% of the asymptomatic subjects during the Shigella sonnei and Shigella flexneri outbreaks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 11 publications
3
80
0
1
Order By: Relevance
“…The relationship between specific serum antibody levels and disease severity has been found in other bacterial and viral infections (24,45). In previous studies of Shigellu-specific antibody responses, only the Ig class, expressed as relative titres, has been reported (6,10,40,43,58), and the relationship between antibody levels and disease severity in natural infection has not been well characterized. In a vaccine study, volunteers who had a clinically more severe response also had higher humoral antibody levels (14), and in a recent report the serum level of anti-LPS IgA was shown to correlate with oral temperature in shigellosis (32).…”
mentioning
confidence: 99%
“…The relationship between specific serum antibody levels and disease severity has been found in other bacterial and viral infections (24,45). In previous studies of Shigellu-specific antibody responses, only the Ig class, expressed as relative titres, has been reported (6,10,40,43,58), and the relationship between antibody levels and disease severity in natural infection has not been well characterized. In a vaccine study, volunteers who had a clinically more severe response also had higher humoral antibody levels (14), and in a recent report the serum level of anti-LPS IgA was shown to correlate with oral temperature in shigellosis (32).…”
mentioning
confidence: 99%
“…Several assays can be considered as immunological functional readouts to determine effectiveness of antibodies raised upon vaccination, like opsonophagocytosis or serum bactericidal assay, to determine cell-mediated and cell-independent bactericidal activity of antibodies respectively (20). Although not being an established correlate of protection for Shigella effectiveness, ability to cause complement mediated killing has been assessed several times in sera both from convalescent patients and from vaccinated individuals (3, 4, 7). An in vitro assay to assess complement mediated killing represents a key indication of functional activity of antibodies raised upon vaccination with Shigella vaccine candidates, and this assay is traditionally represented by the SBA.…”
Section: Discussionmentioning
confidence: 99%
“…Although several approaches have been tried during the years by several groups worldwide, no vaccines are licensed yet. Among the different approaches used to produce Shigella vaccines, many of the candidate vaccines target the serotype-specific O-Antigen (OAg) part of the lipopolysaccharide (LPS), as OAg has been identified as a key antigen recognized by the immune system after natural infection (3). In fact, although multiple immune mechanisms may provide protection against Shigella and are not yet fully elucidated, it is well established that antibodies directed to OAg can fix complement and kill target bacteria in a serotype-specific manner (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have been published where the serological response in Shigella patients has been studied. Cohen et al [15] showed by ELISA that, in paired serum samples from 13 S. flexneri patients, 15.4% showed a significant antibody rise against S. sonnei LPS, also mentioning that part of the population was probably previously exposed to S. sonnei.…”
Section: Discussionmentioning
confidence: 99%